Presymptomatic testing for Huntington's disease in the United Kingdom. The United Kingdom Huntington's Disease Prediction Consortium. Issue 6842 (20th June 1992) - Tyler, A.; Ball, D.; Craufurd, D.
Abstract : OBJECTIVE–To evaluate the United Kingdom Huntington's disease presymptomatic testing programme. DESIGN–Postal questionnaire survey to collect data on all tests performed by clinical genetics centres between 1987 and 1990. SETTING–Genetic centres providing presymptomatic testing in the United Kingdom. SUBJECTS–248 subjects at risk of Huntington's disease who had presymptomatic testing at their request. MAIN OUTCOME MEASURES–Sex, age, prior risk, and risk after testing. RESULTS–The risk of carrying the Huntington disease gene was reduced for 151 (61%) of the applicants and raised for 97 (39%). 158 (64%) of the subjects were female and 90 (36%) male. The median age at which the results were given was 32.5 years. CONCLUSIONS–The demand for testing was lower than expected and may have reached its peak in 1990. The excess of low risk results was not fully explained by the age effect. All the genetics centres concerned have agreed a common service protocol which requires extensive pre-test counselling and post-test follow up. The worth of the procedure remains to be decided. The availability of a large body of pooled data from all the United Kingdom testing centres, which individually are likely to have only a few results, will form a valuable resource for monitoring the long term psychosocial impact of testing.